2012
DOI: 10.1111/j.1600-0412.2012.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological gender of patients with polycystic ovary syndrome

Abstract: Women with PCOS have, depending on age and severity of disease, problems with psychological gender identification. Duration and severity of PCOS can negatively affect the self-image of patients, lead to a disturbed identification with the female-gender scheme and, associated with it, social roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
(15 reference statements)
0
9
0
3
Order By: Relevance
“…It was observed that younger PCOS women are more influenced by the biological sphere, particularly worries related to menstrual disorders and infertility. On the contrary, adult PCOS women behave more often as sexually undifferentiated due to a weakened self-assessment in terms of biological maturity and social role (171).…”
Section: Psychological Symptoms and Heath-related Quality Of Life In mentioning
confidence: 99%
“…It was observed that younger PCOS women are more influenced by the biological sphere, particularly worries related to menstrual disorders and infertility. On the contrary, adult PCOS women behave more often as sexually undifferentiated due to a weakened self-assessment in terms of biological maturity and social role (171).…”
Section: Psychological Symptoms and Heath-related Quality Of Life In mentioning
confidence: 99%
“…Similar study assessing influence of PCOS and concomitant hirsutism on psychological gender, was conducted by Kowalczyk et al [26]. Authors did not find differences between the PCOS women and control group in terms of age, height, weight, BMI, marital status or education level.…”
Section: Introductionmentioning
confidence: 55%
“…In the study by Kowalczyk et al [23], a subgroup of women with PCOS aged 23-30 years did not demonstrate problems with psychological gender roles. However, women older than 30 years often viewed themselves as sexually undifferentiated compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The duration and severity of PCOS can negatively affect the self-image of a patient and lead to a disturbed identification with the female-gender scheme. Women are less likely to identify with a FGS, and more likely to see themselves as androgynous [23].…”
Section: Prace Oryginalnementioning
confidence: 99%